GRAMMATICAL ERRORS ON THE ESSAY WRITTEN BY THE THIRDSEMESTER STUDENTS OF ENGLISH DEPARTMENT STUDY PROGRAM, STKIP AL MAKSUM LANGKAT - Donny Adiatmana Ginting (The Seall Journal, 2020)
This research aims to analyse the grammatical errors made by the students in writing the English essay. The author uses the types ofgrammar in academic writing proposed by Yakhontova (2003). The research design is descriptive qualitative, and the technique ofanalysing the data is content analysis. Based on the analysis, there are five grammatical errors made by students. The errors are spelling,noun, subject-verb agreement, punctuation and pronoun. The students made errors in spelling with the total error is 16% and made errors innoun with the total error is 16%. Furthermore, the students made errors in punctuation with the total error is 28 % and made errors inpronoun with the total error is 20 %. The students made errors in pronoun with the total error is 20 %. Punctuation is the most errorsmade by the students in writing the essay.